(untitled) (PRÁXIS EM SAÚDE, 2025)
This work aims to discuss three fundamental elements of psychotherapy with children: bond, play, and listening. The therapeutic bond serves as the foundation for building trust and emotional security. Play is understood as the central language of childhood and a means of symbolic expression. Listening, in turn, involves sensitive receptivity and attention to the various forms of child communication. The articulation of these elements promotes emotional development and strengthens the child’s psychological resources, being essential for an ethical, affective, and effective clinical practice. Methodologically, the writing was structured based on an integrative literature review. The results of this review highlighted the importance of these elements. Considering the complexity of the child therapeutic process, it is essential that psychotherapy continues to be conducted in a flexible and integrated manner, taking into account each child’s specificities and the various therapeutic approaches.